Turkey-Iran rivalry in the changing geopolitics of the South Caucasus - Hamidreza Azizi; Daria Isachenko (Stiftung Wissenschaft und Politik (SWP), 2023)
The South Caucasus has long been a theatre of Turkish and Iranian cooperation and rivalry. While these two regional powers have historically balanced their interests, there are signs that rivalry is taking precedence. Turkey's unwavering backing of Azerbaijan during the 2020 Karabakh War consolidated Ankara's footprint in the region. Azerbaijan's retaking of the rest of Karabakh in the latest military strikes on 19 September 2023 makes a peace accord between Azerbaijan and Armenia more likely, furthering Turkey's interests, and potentially limiting Russia's role in the region. However, the prospect of a "less Russia, more Turkey" dynamic heightens Tehran's apprehensions towards Ankara. Particularly concerning for Iran is the clause within the Moscow-brokered ceasefire of November 2020 that mandates the rebuilding of a road and rail link connecting Turkey to mainland Azerbaijan via Azerbaijan's Nakhchivan exclave and Armenia's south-eastern Syunik province; this risks marginalising Iran. In addition, Tehran is anxiously observing the deepening of ties between Turkey's close ally, Azerbaijan, and Iran's key adversary, Israel.
Keywords: 320; South Caucasus; Turkey; Iran; Russia; Armenia; Azerbaijan; 2020 Karabakh War; Nakhchivan exclave; Zangezur Corridor